Administrative Perspectives on the Implementation and Sustainability of State-Supported Health Insurance Schemes in Nigeria: A Descriptive Qualitative Study - Effiong Fortune Benjamin; Hassan Ibrahim Adebayo; Dine Roseline Dzekem; Olawuyi Dimeji Abdulsobur; Adewole David Ayobami (My University, 2024)
Background: Since the state-supported health insurance schemes (SSHIS) began in Nigeria, perspectives of implementers and other administrative actors have been under-documented in the program evaluations. Bridging this information gap is crucial to addressing the challenges impeding the scheme's impact. Therefore, this study investigated the administrative stakeholders' perspective on the implementation and sustainability of the SSHIS in Nigeria. Methods: This study adopted a descriptive qualitative design. Participants were state actors, public and private healthcare providers, and ward committee members purposely selected from six states with a functional SSHIS, representing Nigeria's six geo-political zones. The states included Cross River (South-South), Enugu (South-East), Oyo (Southwest), Kwara (North-Central), Sokoto (Northwest) and Taraba (Northeast) states. 30 key informant interviews (KII) were conducted among these stakeholders exploring the design, successes, challenges, and personal recommendations relating to the SSHIS operation in their states. Data analysis was performed using NVIVO version 11. Results: Across the states, the SSHIS design was adaptive covering formal, informal, and low-income vulnerable groups. Reported impact of the scheme related to improved state health indices, infrastructure, access equity, and funding systems. Challenges threatening the coverage and sustainability of the SSHIS included low public awareness and buy-in and other governmental (processes and payments), economic (funding and costs), manpower, and environmental (insecurity and facility inaccessibility) factors to which possible corrective measures were suggested. Conclusion: Administrators offer critical policy action points to enhance SSHIS impact in Nigeria towards universal health coverage. Future studies may investigate the key challenges and the effectiveness of the suggested solutions.
Ethical approval was obtained from the National Health Research Ethics Committee (NHREC/01/01/2007-04/08/2023), and ethical committees of various state ministries of health. Written informed consent was also obtained from every respondent of the study. A letter of introduction was written to all the KII stakeholders who participated in the study.
Keywords: Health Insurance; Implementers; Stakeholders; SSHIS; States; Nigeria.